Calvin dan Humanisme - Agustinus M.L Batlajery (Jurnal Ledalero, 2016)
Many researches have been done concerning the contexts and the factors which effected the theology and character of John Calvin. At least three contemporary scenes should be considered as the dominant context when speaking about Calvin. First, the Rome from which the Reformer seceded; second, the Anabaptists; and third, the humanists especially Renaissance humanism. This essay looks at the core of Renaissance humanism, namely its emphasis on the Greek and Latin classics as the chief subject of study and as unrivalled models of imitation and in thinking and even in actual conduct. After a brief glance at Calvin’s education, this essay attempts to explain the influence of Christian French humanism on Calvin in his ethics and theology, and its ongoing relevance to our contemporary situation in Indonesia today. Keywords: Calvin, humanism, classical writings, theology, character, sense of discipline, discipline humaniores ---------------------------------------------------------------------------------------------------------------------- Banyak penelitian telah dilakukan mengenai konteks dan faktor-faktor yang berpengaruh terhadap teologi dan karakter Yohanes Calvin. Setidaknya ada tiga hal mendasar yang harus dianggap penting sebagai konteks yang dominan ketika berbicara tentang Calvin. Pertama, Roma dari mana Reformer memisahkan diri; kedua, Anabaptis; dan ketiga, para humanis terutama humanisme Renaisans. Esai ini memperlihatkan inti dari humanisme Renaisans, yang bertitik tolak pada Yunani dan Latin klasik sebagai model tak tertandingi mengenai imitasi, hal berpikir, dan perilaku aktual. Setelah melihat sekilas pendidikan Calvin, esai ini mencoba menjelaskan pengaruh humanisme Kekristenan Prancis terhadap etika dan teologi Calvin, dan relevansi berkelanjutan bagi situasi kontemporer kita di Indonesia saat ini. Kata-kata kunci: Calvin, humanisme, tulisan-tulisan klasik, teologi, karakter, rasa disiplin, disiplin humaniores.